Microbiota of newborn meconium is associated with maternal anxiety experienced during pregnancy. Issue 5 (25th March 2019) - Hu, Jianzhong; Ly, Jenny; Zhang, Wei; Huang, Yonglin; Glover, Vivette; Peter, Inga; Hurd, Yasmin L.; Nomura, Yoko
Abstract: Little is known about whether a mother's psychological state during pregnancy influences her offspring's microbiome. This study examined whether maternal anxiety, depression, and stress during pregnancy is associated with the diversity of meconium microbiome, the first internal discharge, in 75 newborns from an existing birth cohort study. The meconium microbiome was profiled using multibarcode16S rRNA sequencing at V3‐V4 hypervariable region followed by taxonomic assignment to the green gene 16S references at 97% similarity and diversity analysis at the genus level. Results showed that the meconium contained diversified microbiota, and greater pregnancy‐related anxiety was significantly associated with a less diverse meconium microbiota community ( p = 0.001). At the specific taxa level, greater pregnancy‐related anxiety was correlated with a lower level of the Enterococcaceae family ( p = 2e‐4, Spearman rho = −0.43). These findings support a significant role of prenatal maternal mood in the early‐life bacteria colonization of their offspring.